Clinical aspects and endoscopic findings of caustic ingestions in children in Dakar, Senegal - Abou BA; Ndèye Fatou Sow; Aliou Thiongane; Amadou Sow; Babacar Niang; Younoussa Keïta; Aminata Mbaye; Awa Kane; Ousmane Ndiaye (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2023)
Introduction: Caustic ingestion is a rare event, most often accidental in children, which can lead to lesions of varying severity in the digestive tract. The aim of this study was to describe the clinical aspects and endoscopic findings of caustic ingestions.  Methods: This is a retrospective, descriptive, and analytical bicentric study carried out at the Albert Royer Children's Hospital and the Dalal Jamm Hospital in Dakar. Children who had ingested a caustic product and undergone upper gastrointestinal endoscopy during the period May 1, 2020, to July 31, 2023, were included. Lesions were classified according to the Zargar classification. Results: A total of 35 children (23 boys; 65.7%) were included. The mean age was 25,1 ± 19,03 months, with a predominance of the 12-23 months age group (53.13%). Bleach (55.88%) was the most ingested caustic, followed by soda (26.47%). Oral erythema (29%) and erosions (22.5%) were the main physical signs; most often in the case of soda ingestion (90%; p = 0.004). Esogastroduodenal endoscopy showed lesions in 37,14% of children classified as stage I (17,14%), stage IIa (14.29%), and stage III (5.71%). The presence of labial or oral lesions was not significantly associated with the occurrence of digestive lesions (p = 0.37).  Conclusion: Caustic ingestion is an accidental event in children. Bleach was the most ingested caustic. Caustic lesions of the digestive tract were dominated by erythema and ulceration.